Role of Mn-substitution towards the enhanced hydrogen storage performance in FeTi. (19th February 2022) - Padhee, Satya Prakash; Roy, Amritendu; Pati, Soobhankar
Abstract: The role of Mn substitution in FeTi towards the hydrogenation kinetics and hydrogen storage capacity was investigated using a combination of experimental and theoretical tools. Pristine and Mn-substituted FeTi was produced by electro-deoxidation of oxide precursors, such as natural ilmenite, titania and manganese dioxide. The produced materials were evaluated for hydrogen storage capacity. Ab-initio density functional theory (DFT) calculations were performed to understand the thermodynamics and kinetics of hydrogen absorption in pristine and doped FeTi. DFT calculations demonstrate that although thermodynamic and kinetic parameters of hydrogen absorption with Mn substitution is similar to those in the pristine FeTi, oxygen affinity of Mn at the surface is higher than Fe or Ti. We conclude that Mn acts as a sacrificial oxidizing element and oxidizes more readily at the surface over Fe or Ti, resulting in easy activation of the FeTi alloy. We show superior cyclic-hydrogen absorption behavior in bulk in FeTi with Mn substitution. After 20 charge-discharge cycles, the measured hydrogen storage capacity of FeTi with Mn substitution was steady ∼120 mA h/g (0.8 wt %), which is noticeably higher than that of pristine FeTi. The experimental and theoretical results shows that in case of a practical hydrogen storage scenario, Mn substitution will benefit in reducing absorption fatigue in FeTi. Further, most likely it may not be possible to use pristine FeTi phase. Graphical abstract: Image 1 Highlights: Electro-deoxidation synthesis of Mn-substituted FeTi using oxide precursors. Improvement in hydrogen capacity retention over 20 cycles using electrochemical measurements. Establish the relation of hydrogen capacity retention and Mn addition using density functional theory (DFT).